The relation of basic self‐disturbance to self‐harm, eating disorder symptomatology and other clinical features: Exploration in an early psychosis sample. Issue 3 (2nd July 2019) - Rasmussen, Andreas R.; Reich, Daniel; Lavoie, Suzie; Li, Emily; Hartmann, Jessica A.; McHugh, Meredith; Whitford, Thomas J.; Nelson, Barnaby
Abstract : Background and Aims: The notion of basic self‐disturbance has been proposed as a core feature of schizophrenia‐spectrum disorders and as an indicator of future transition to psychosis in high‐risk populations. However, the relation of this notion to many clinical characteristics has not been explored. The aim of this study was: (a) to investigate the distribution of self‐disturbance and other symptoms dimensions in ultra‐high risk (UHR), first‐episode psychosis (FEP) and healthy control groups; and (b) to explore the association of self‐disturbance with a history of self‐harm, suicidal attempt, eating disorder symptomatology, school bullying victimization and sexual or physical abuse. Methods: Patients with UHR status (n = 38) or FEP (n = 26) and healthy controls (n = 33) were assessed with the Examination of Anomalous Self‐Experience (EASE) and the Comprehensive Assessment of at Risk Mental States (CAARMS). The clinical‐historical variables were assessed through medical records. Results: The FEP group scored significantly higher on the EASE than the UHR group, which scored significantly higher than the healthy control group, which had a very low score. Multivariate logistic regression analyses revealed that higher EASE score was significantly associated with a history of self‐harm, disordered eating and bullying victimization (but not with suicide attempts or sexual/physical abuse) after controlling for positive, negative and depressive symptoms. Conclusion: These novel findings suggest that self‐disturbance may be related to a history of school bullying victimization, self‐harm and eating disorder symptomatology in patients with or at‐risk of psychosis. If further confirmed, these findings are potentially relevant to clinical risk assessment and therapy.